Clinical Performance Evaluation of VersaTrek 528 Blood Culture System in a Chinese Tertiary Hospital - Yue, Pinli; Zhou, Menglan; Kudinha, Timothy; Xie, Xiuli; Du, Juan; Song, Hongmei; Zhang, Lintao; Ma, Xiaojun; Weng, Li; Chai, Wenzhao; Zhu, Huadong; Yang, Qiwen; et al. (Frontiers in Microbiology, 2018)
Background: The aim of this study was to evaluate the clinical performance of VersaTrek 528 compared to BACTEC FX 400 blood culture systems. Materials and Methods: Simulated and clinically obtained blood cultures (BC) were used in the study. Confirmed bacterial species (n =78), including 43 Gram-positives, 30 Gram-negatives, and 5 Candida albicans strains, were each inoculated into BC bottles. Clinically obtained BCs were subdivided into two groups, A and B. In group A were 72 BC sets (pair: aerobic and anaerobic) in which a set inoculated with 5 ml blood was processed in the VersaTrek BC system, whilst the one inoculated with 10 ml blood was processed in the FX BC system. In group B, 76 BC sets (pairs) corresponding to 152 VersaTrek bottles and 152 FX bottles were inoculated with the same volume (10 ml) of blood, and processed in each system. Results: In the simulated BC study, 90% (63/70) of the VersaTrek aerobic bottles were positive, which was higher than that of FX 400 (59/70, 84%), but was not statistically significant (P = 0.423). In contrast, FX 400 anaerobic bottles had a higher positive rate than the other BC system (84% vs 77%), although it was statistically insignificant (P = 0.267). Time to detection of organisms in the two BCs was comparable for both aerobic (P=0.131) and anaerobic bottles (P=0.104). In clinical BCs of group A, FX BC system had slightly higher positive rates for both aerobic (11.1% vs 9.7%, P=0.312) and anaerobic (8.3% vs 6.9%, P=0.375) bottles. However, the difference was not statistically significant. In group B, VersaTrek aerobic bottles had a higher positive rate compared to the other BC system (10.5% vs 5.2%, P=0.063). In terms of positive rates of sub-studies A and B, VersaTrek and FX BC systems were comparable. Conclusion: There was no significant difference between the two BC systems in the detection of bacteria and fungi in simulated BCs. In clinical BCs, the performance of the VersaTrek BC system, with inoculation of 5 ml or 10 ml patient’s blood, was comparable to the FX system with inoculation of 10 ml patient’s blood.